Stereotactic ablative radiotherapy for acquired resistance to EGFR therapy in metastatic non-small cell lung cancer - Chicas-Sett, Rodolfo; Castilla Martinez, Juan; Hernández Blanquisett, Abrahan; Zafra, Juan; Pastor-Peidro, Jorge (Frontiers in Oncology, 2023)
The advent of targeted therapy has transformed the treatment paradigm and survival of patients with metastatic non-small cell lung cancer (NSCLC) with driver mutations. The development of acquired resistances during treatment with tyrosine kinase inhibitors (TKIs) impedes a prolonged survival in many patients. This fact is leading to the use of locally ablative therapies such as stereotactic ablative radiotherapy (SABR) to counter these resistances. SABR is a non-invasive treatment that can be delivered in multiple locations and has already proven effective in oligometastatic disease. Clinical evidence suggests that the combination of SABR with TKIs prolongs progression-free survival (PFS) in metastatic NSCLC patients with mutations in epidermal growth factor receptor (EGFR), with international guidelines recommending their use in unfavorable scenarios such as oligoprogressive disease. In this publication, we have reviewed the available evidence on EGFR-TKIs resistance mechanisms and the combination of SABR with TKI in metastatic NSCLC with EGFR mutations. We also describe the utility and clinical recommendations of this combination in oligometastatic and oligoprogressive disease.